ARSITEKTUR RUMAH TRADISIONAL DI MALUKU 1 (Studi Etnoarkeologi) - Lucas Wattimena (Balai Arkeologi Yogyakarta, 2013)
South Ceram coastal communities consist of several groups, among others: Noa nea, Simalouw, Yalatan and Rohua. Each group has a hallmark of culture, as the identity of each society. It is manifestated - among other - in the traditional architecture. The meaning of traditional architecture here is the traditional house, where the traditional house on the south coast of Ceram Island, is not merely seen as a physical building but also has the structure (roles, functions and position) in the development of the society.it could be seen in the pattern of traditional houses. The research showed that the traditional houses had different structure (roles, functions and positions), but on the other those variety of function are then adapted to their roles according to the southtern coastal communities of Ceram island (Noa Nea, Rohua, Yalatan) traditional houses can be grouped into traditional houses and big houses.